Gender and Marriage: The Case of the Ordained Women in the Presbyterian Church of Ghana - Adasi, Grace Sintim (EBSU Journal of Social Sciences and Humanities, 2021)
The paper is concerned with the ordained women in the Presbyterian Church of Ghana (PCG) and how gender prescribes roles in their marriages and in the PCG. Gender refers to the social attributes and opportunities associated with male and female and their relationships are socially constructed, context/time specific. Christianity prescribes to women the role they must play in their matrimonial homes. Women played major roles in the history of the Basel Mission in the then Gold Coast. However, they are portrayed as wives of missionaries. More precisely, they were seen as mission brides and wives, thus representing virtually the collective property of the Mission. In combining the traditional and contemporary roles, many women find themselves playing the roles as wives, mothers and reverend ministers. The PCG put strong emphasis on family life and the issue of relocation has greatly influenced some of the PCG’s member’s attitude to couple ministry. Thus another traditional practice where women do not take leadership positions when men are around. The study examines the theory of gender discourse as a theoretical frame using historical analysis method. The existing structures within both the church and society are patriarchal and the structures turn to focus more on men than on women in the various sectors of life. In the field work, the researcher came across an ordained couple where the wife was ordained first, went into the ministry first, in terms of educational qualification she is more qualified than the husband and they were put in the same district but the husband was rather appointed by the PCG as the district minister for the wife to be his subordinate. The African culture assigns women in the family to the domestic domain denying them from decision making positions in the church but women and men should act in partnership.